Green synthesis of ZnS/MoS2-decorated porous carbon for photocatalytic degradation of tetracycline under visible light - Zahra Amiri; Hosein Banna Motejadded Emrooz; Mobin Safarzadeh Khosrowshahi (Scientific Reports)
Abstract This study investigated a one-step green pyrolysis method inspired by chemical vapor deposition, utilizing melamine and zinc nitrate precursors with varying sulfur content for degradation and adsorption of tetracycline. The method effectively synthesized a ZnS/MoS2 heterojunction composite supported on a porous carbon substrate. It takes advantage of the gases (such as CO2, CO, and H2O) naturally released during pyrolysis to serve as internal activating agents. In contrast to traditional techniques that rely on inert atmospheres, chemical additives, or complicated high-temperature setups, this method minimizes both the ecological footprint and procedural complexity. The optimal composite, PCS2 (synthesized with 2 g of sulfur), exhibited the lowest band gap of 2.91 eV and the highest specific surface area of 216.83 m2 g−1, making it the most effective among the tested samples. This composite achieved 55% adsorption of pollutants and demonstrated a total removal efficiency of 81% for tetracycline. The addition of scavengers revealed that the primary active species in the reaction were holes. This synthesized method shows great promise for preparing heterojunction structures, making it highly suitable for removing organic pollutants from contaminated water.